Пропозициональные логики доверия - Бурдюк, В.Я. (Кибернетика и системный анализ, 2011)
Пропозицiйнi логiки довiри мають справу з такими твердженнями, якi сприймаються на рiвнi довiри–недовiри у дiапазонi вiд 51% до 100%. Доведено, що закони цих логiк i закони двозначної логiки мають однакову форму. Propositional trust logics deal with propositions that are considered at a trust-distrust level from 51% to 100%. The rules of these logics and rules of 2-valued logic are proved to be of the same form.